POLITICAL TRENDS OF CARICATURE: (in Al-Sharq Al-Awsat Newspaper) - Al-Salem, Hamdan (ALBAHITH ALALAMI, 2008)
The importance of studying the political trends of caricature in Al-Sharq Al-Awsat Newspaper comes from the importance of this magical and satirical journalistic art, as it addresses various trends with satirical criticism that exposes the negative sides and affects the reader’s consciousness in a way or another by contributing to the public opinion about these issues and topics that affect people's lives and their future. Therefore, this art is no less important than the other arts, on the contrary, it complements the other arts and also contributes to the importance of Journalism. Also, the choice of Al-Sharq Al-Awsat Newspaper as being one of the most widely circulated and prominent Arab newspapers, they also give an importance to caricature in a very unique way, it also gets special care as it is used in almost any issue, such as articles, commentaries, investigation, dialogues, and journalistic arts in general. The problem of this research resides in a series of questions as shown below:1- what are the main political trends contained in Caricatures ?2- In which way Caricatures are shown ?Based on the importance of the research and its problem, the objectives of this research  became clear in answering the questions, as it became possible to have a look at the contents of the Caricatures (The research’s topic) as well as the ideas, types and characters, therefore identifying the task done by these Caricatures whether it was uncovering the problematics of phenomena or discussing them or just directing the public opinion against them. By determining the issues of these Caricatures and ideas, repetitions and percentages and also the position they held in Journalism.It is clear from the foregoing that the analysis of Caricatures in the newspaper Al-sharq Al-Awsat during the time set by the research, has been focused mainly on the Israeli–Palestinian conflict which the center of the Arab world conflict, as well as on the Iraqi issue that involves several complex political crises represented through Caricatures and media in general, while the global issues came afterwards.         We can say that Caricaturists were able to deliver messages to the Arab reader through their drawings, where they can extend their ideas and visions leaving it for the reader to make up his own perception about political events and global crises while inviting him to have an opinion about them. Perhaps this is the educational and informative intention the Caricaturists want to give, which seeks a global communication to be established.